Explaining the off-the-books enterprise culture of Ukraine: reluctant or willing entrepreneurship?. (10th May 2010) - Williams, Colin C.; Round, John; Rodgers, Peter
In recent years, there has been a growing realisation that beyond the realm of legitimate entrepreneurship is a large, hidden enterprise culture composed of entrepreneurs conducting some or all of their trade off-the-books. Until now, however, few have evaluated how many entrepreneurs start-up their ventures trading off-the-books and why they do so. Reporting face-to-face interviews conducted in Ukraine during 2005-2006 with 331 entrepreneurs, the finding is not only that the vast majority (90%) operate partially or wholly off-the-books, but also that they are not all driven by necessity, as a last resort and as a survival strategy into entrepreneurship. Revealing how many are willing rather than reluctant entrepreneurs; and that even those who were initially reluctant and ventured into it out of necessity, became more willing entrepreneurs over time as their business became established – the paper concludes by discussing the implications of these findings for both further research and public policy.